Sustainable Dividend Policies and CSR Disclosure: How Strategic Investors Influence Wealth Distribution - Niklas Heinzel; Rainer Lueg (Corporate Social Responsibility and Environmental Management, 2025)
This study investigates how strategic investors influence the relationship between corporate social responsibility (CSR) disclosure and dividend policy in US firms. Drawing on agency and stakeholder theory, we conceptualize dividends not merely as financial signals but as instruments of stakeholder-oriented wealth distribution. Using panel data from S&P 500 firms (2007–2021) and a fixed effects regression approach, we test whether CSR disclosure affects both the likelihood and the magnitude of dividend payments, and how this relationship is moderated by the presence of strategic ownership (e.g., pension funds, governments, and employee stock plans). We find that CSR disclosure increases both dividend propensity and dividend yield. Strategic investors positively moderate the initiation of dividends but negatively moderate dividend size—suggesting a tension between signaling accountability and preserving long-term capital. These findings enhance our understanding of sustainable governance and offer implications for CSR reporting, ownership design, and financial policy.
Keywords: 650; CSR disclosure; dividend policy; institutional investors; stakeholder governance; strategic ownership; sustainable finance